2019
DOI: 10.1111/dth.12848
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of omalizumab in Cutaneous Mastocytosis: A case series

Abstract: Background: Mastocytosis describes a heterogeneous group of disorders arising from a clonal proliferation of mast cells. Given the lack of curative treatments for the cutaneous form, there is a significant need for superior therapies. Omalizumab is a recombinant DNA‐derived humanized IgG monoclonal antibody that selectively binds to human immunoglobulin E (IgE). It represents a potential treatment for the management of cutaneous mastocytosis, which currently has no standard treatment. Methods: Two patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Recently, omalizumab has been proposed for mastocytosis patients to treat severe mediator-related symptoms and to prevent anaphylaxis (3,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101). The drug was indeed found to be effective in the prevention of recurrent episodes of idiopathic anaphylaxis in adults with mastocytosis (91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101), but has only be licensed for use in children over 12 years of age. The results of the XOLMA study has shown that omalizumab was safe and improved mastocytosis symptoms like diarrhea, dizziness, flush and anaphylactic reactions (100).…”
Section: Management Of Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, omalizumab has been proposed for mastocytosis patients to treat severe mediator-related symptoms and to prevent anaphylaxis (3,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101). The drug was indeed found to be effective in the prevention of recurrent episodes of idiopathic anaphylaxis in adults with mastocytosis (91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101), but has only be licensed for use in children over 12 years of age. The results of the XOLMA study has shown that omalizumab was safe and improved mastocytosis symptoms like diarrhea, dizziness, flush and anaphylactic reactions (100).…”
Section: Management Of Anaphylaxismentioning
confidence: 99%
“…First long-term follow-ups are available with improvement of clinical symptoms in two patients with SM and recurrent anaphylaxis over an observation period of 12 years (99). Several case reports have suggested the usefulness of omalizumab in SM (92) and CM in adults (93), but also in adolescents (94), and children (95). Although the evidence is based only on uncontrolled observations in a small number of patients, this drug is likely to be effective in the prevention of recurrent anaphylaxis in children with or without mastocytosis (97).…”
Section: Management Of Anaphylaxismentioning
confidence: 99%
“…The efficacy of treatment with Omalizumab on different symptoms is summarized in Figure 2 and Table 2 …”
Section: Resultsmentioning
confidence: 99%
“…There is emerging evidence that IL-31 plays a role in pruritus in patients with mastocytosis, suggesting that nemolizumab, a potent anti-IL-31 mono clonal antibody, has the potential to be effective in this group of patients, albeit this suggestion needs to be confirmed in clinical settings (102). Another treatment option for pruritus unresponsive to traditional therapies with antihistamines could be omalizumab, the anti-IgE monoclonal antibody, which might block mast cell activity (103). Interestingly, the NK-1 inhibitor, aprepitant, developed for the prevention of chemotherapy-induced nausea and vomiting, seemed to possess some antipruritic properties, as well as some other NK-1 inhibitors (serlopitant and tradipitant) might also provide some benefit in the treatment of pruritus (104)(105)(106).…”
Section: Pruritus From a Clinical Point Of Viewmentioning
confidence: 99%